The circular RNA circ_0030018/miR-136/migration and invasion enhancer 1 (MIEN1) axis promotes the progression of polycystic ovary syndrome. Issue 3 (1st March 2022) - Xu, Jing; Qu, Qinghua; Liu, Bao; Shen, Liyuan
ABSTRACT: The abnormal expression of circular RNAs (circRNAs) is associated with the progression of polycystic ovary syndrome (PCOS), which commonly causes infertility in women. In this study, we identified the role of circ_0030018 in PCOS. Quantitative polymerase chain reaction (qPCR) was used to detect the expression levels of circ_0030018, microRNA (miR)-136, and migration and invasion enhancer 1 (MIEN1). Cell counting kit-8 and 5-ethynyl-2'-deoxyuridine assays were performed to analyze the proliferation of KGN cells. Apoptosis was analyzed using fluorescence-activated cell sorting. Transwell assays were performed to measure the migration and invasion abilities of cells. qPCR and Western blotting were used to measure the levels of E-cadherin, N-cadherin, Snail, and vimentin. The correlation of circ_0030018 or MIEN1 expression with miR-136 expression was confirmed via luciferase reporter and RNA pull-down assays. Results showed that circ_0030018 expression was upregulated in patients with PCOS and KGN cells. Knockdown of circ_0030018 suppressed the proliferation, migration, and invasion of cells, while promoting their apoptosis. circ_0030018 sponged miR-136, which targeted MIEN1. Moreover, downregulation of miR-136 abrogated the effects of circ_0030018 silencing, while the overexpression of MIEN1 reversed the miR-136-induced effect on KGN cells. In summary, loss of circ_0030018 delayed the progression of PCOS via the miR-136/MIEN1 axis. GRAPHICAL ABSTRACT: uf0001